PENERAPAN MODEL PBL BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF WORDWALL DALAM UPAYA MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - Prastiwi, Eka; Halidjah, Siti (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to increase motivation in learning science by using the PBL model assisted by wordwall interactive media among class VA students at SD Negeri 30 Pontianak Selatan. This is a classroom action research with 4 steps, namely, planning, implementing, observing and reflecting. This research was carried out in collaboration with class teachers and colleagues. The subjects of this research were 19 students of class VA at SD Negeri 30 Pontianak Selatan which is consisting of 9 males and 10 females. The data collection techniques are observation and questionnaires. The data analysis technique is qualitative description, which is after the data is found and organized, it will be described by the researcher's opinions or views and data support from various relevant theories. Observation or direct observation of the implementation of learning carried out in 3 cycles. There was an increase on students' learning motivation. In cycle 1 the average motivation showed 63.5%, in cycle 2 it showed 75% and in cycle 3 it showed 82.1% of students' learning motivation. The results of the research show that the learning motivation of class V A students at SDN 30 Pontianak Selatan is relatively high. The results of the analysis also show that the implementation of the PBL model assisted by Wordwall interactive media has a big influence on increasing the learning motivation of class V A students, especially in science subjects.